The Effect of Low-Level Laser Therapy on Accelerating Tooth Movement in Orthodontic Patients: A Randomized Controlled Trial - Mohammad K. Alam; Mohammad Y. Hajeer; Dalia A. Alanazi; Shahad A. Alanazi; Haya O. Alruwaili (Journal of Pharmacy and Bioallied Sciences)
Background: An adjuvant treatment, known as low-level laser therapy (LLLT), has been suggested to quicken orthodontic tooth movement and perhaps shorten the course of treatment. Materials and Methods: For 60 orthodontic patients aged between 15 and 25, a randomized controlled experiment was carried out (30 males and 30 females). Two groups, Group A (LLLT group, n = 30) and Group B (control group, n = 30), were randomly allocated to the participants. For the first 8 weeks of therapy, Group A got LLLT three times a week using a diode laser with a wavelength of 808 nm and a power output of 100 mW. The laser was delivered for 30 s on each side of the target tooth. Beyond routine orthodontic care, Group B did not get any extra care. Using computerized models, the rate of tooth movement was monitored every 2 weeks for a duration of 12 weeks. The degree of tooth movement was the main result; patient-reported discomfort and gingival health were the secondary outcomes. Results: The group that had LLLT (Group A) demonstrated a notably elevated frequency of tooth movement in contrast to the control group (Group B). Group A’s average monthly tooth movement was 1.2 mm, whereas Group B’s average monthly movement was 0.8 mm (P < 0.01). Furthermore, throughout the early phases of therapy, patients in the LLLT group reported less discomfort, and there were no significant variations in gingival health between the two groups. Conclusion: With its ability to speed orthodontic tooth movement, LLLT may shorten the course of therapy. Additionally, it seems to lessen pain while starting orthodontic therapy.